Paediatric Stroke: Review of the Literature and Possible Treatment Options, including Endovascular Approach. (19th June 2011) - Ciceri, Elisa F.; Cuccarini, Valeria; Chiapparini, Luisa; Saletti, Veronica; Valvassori, Luca
Abstract : Stroke is among the top 10 causes of death in childhood. More than half of the surviving children have long-term neurological sequelae. Ischemic stroke (IS) includes arterial ischemic stroke and cerebral venous thrombosis with venous infarction. Haemorrhagic stroke (HS) includes intracerebral haematoma or subarachnoid haemorrhage. Risk factors for stroke are different in children and in adults. 10–30% of IS have no identified risk factors. However, multiple risk factors are recognizable in the majority of stroke in children; thus, a comprehensive diagnostic evaluation is crucial. Vascular abnormalities, such as arteriovenous malformations, aneurysms, vessel dissection, stenosis, and moyamoya disease, are frequently associated with both IS and HS and lead to high recurrence rates. Endovascular and surgical treatment options are sometimes indicated, performed on the basis of expert opinion, and extrapolated from the adult procedures. In the present paper, we review the recent literature and we discuss the treatment in five cases managed at our institutions.